A Narrative Review on the Role of Pharmacology in Nursing Care: Advancing Safe and Effective Medication Management - Abdulrahman Salman Alamri,; Abdulrahim Saadallah Alharbi,; Mansour Saleh Alghamdi,; Muteb Ali Alzahrani,; Ibrahim Baalqasim A Alfaqih,; Khaled Saeed Alzahrani,; Hamdi Jaber H Alqarni,; Bader Nasser S Alghamdi,; Sulaiman Faisal Alrabie,; Fahad Abdullah Al-garni, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Pharmacology is a cornerstone of nursing care, enabling nurses to administer medications safely, monitor for adverse effects, and educate patients effectively. However, challenges such as insufficient pharmacological education, complex medication regimens, and systemic barriers can compromise patient safety. Objective: This narrative review aims to explore the role of pharmacology in nursing care, emphasizing its impact on medication management and patient outcomes, while identifying challenges and proposing solutions to improve nursing practice. Methods: A comprehensive search of peer-reviewed literature, clinical guidelines, and textbooks published in the last 15 years was conducted using databases such as PubMed, CINAHL, and Scopus. Key terms included “pharmacology,” “nursing care,” “medication management,” and “patient safety.” Articles focusing on the integration of pharmacology into nursing practice were thematically analyzed to synthesize key findings. Results: The review identified that robust pharmacological knowledge is essential for safe medication administration and reducing errors. However, gaps in nursing education, high workloads, and limited access to training programs remain significant barriers. Interprofessional collaboration and the use of technological tools such as decision-support systems were found to enhance medication safety and nursing practice. Conclusion: Strengthening pharmacological education, promoting continuous professional development, and leveraging technology are crucial to addressing challenges in medication management. Future research should focus on the long-term impact of pharmacological training on nursing competencies and patient outcomes, as well as innovative strategies for resource-limited settings.